FEASIBILITY OF EARLY SURGICAL INTERVENTION IN POSTOPERATIVE ENTERO-CUTANEOUS FISTULAE - Sheikh, Abdul Razaque; Malik, Arshad M; Sheikh, Gulshan Ara (Journal of Ayub Medical College Abbottabad, 2010)
Objectives: To study the out come and benefits of an early surgical intervention in postoperative entero-cutaneous fistulae. Methods: It’s a retrospective descriptive study conducted at department of surgery LUMHS from Jan 2001 to November 2008. Two hundred and thirteen (213) post-operative fistulae are included as study subjects while those due to inflammatory bowel diseases, road traffic accidents or following blunt, stab or gunshot abdominal trauma are excluded. An aggressive treatment to build up nutritional status, correction of anaemia and control of sepsis was followed by surgical intervention as soon as the patient’s condition permitted. Variables such as type of fistula, out put per 24 hours, duration since development , complications due to fistula, nutritional status, operative procedure, operative time, post-operative complications, total post-operative stay, follow up schedule, outcome. The results were statistically analysed on SPSS-12. Results: A total 213 patients comprising 184 males (85.6%) and 29 (13.5%) females with a mean age of 36.08 years and a range of 64 (78-14) years presenting with post-operative enter-cutaneous fistula are included in the study. Maximum number of patients (171, 79.5%) developed fistula between 4th-6th postoperative day and a vast majority of fistula occurred in the ileum (207, 97.18%) either as a result of anastomotic failure (103), leak from primary closure (99) or from un-noticed missed perforations (5). Of the total number, 24 patients eventually died making a mortality of 11.2%. Early surgical intervention proved life saving (p<0.001). A strong relation was found pre-operative albumin levels and surgical closure of the fistula (p<0.001) and associated mortality (p<0.001). Conclusion: High out put fistula is unlikely to close spontaneously on conservative measures. Early surgical intervention can be life saving. Keywords: Entero-cutaneous fistula, early surgical intervention, morbidity, mortality